2023
DOI: 10.3390/buildings13010135
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Mechanical Behavior of Self-Centering Joint between CFDST Column and RC Beam

Abstract: The existing connection between the concrete-filled double steel tubular (CFDST) column and the reinforced concrete (RC) beam is difficult to repair and reuse after damage. In this paper, a self-centering joint between the CFDST column and the RC beam is proposed. The self-centering of the joint is realized by prestressed steel strands, and the energy dissipation is realized by friction. The overall purpose of the research is to analyze the influence of steel strand and friction on the mechanical behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…[10][11][12]. To promote the application of self-centering structural components in engineering, Yan et al [13] proposed a self-centering joint between CFDST columns and RC beams. Analytical studies have shown that increasing the friction can improve joint energy dissipation, but it will increase the residual deformation of the joint.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12]. To promote the application of self-centering structural components in engineering, Yan et al [13] proposed a self-centering joint between CFDST columns and RC beams. Analytical studies have shown that increasing the friction can improve joint energy dissipation, but it will increase the residual deformation of the joint.…”
Section: Introductionmentioning
confidence: 99%